2018
DOI: 10.1002/jmri.26175
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of breast mass morphology with diffusion‐weighted MRI: Beyond apparent diffusion coefficient

Abstract: 3 Technical Efficacy: Stage 2 J. Magn. Reson. Imaging 2018;48:1668-1677.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 36 publications
1
18
0
Order By: Relevance
“…On the other hand, there is a growing interest in the development of contrast-agent free protocols by using the acquisition of diffusion-weighted images (DWI) and their respective Apparent diffusion coefficient (ADC) maps [69] , [70] , [49] , [71] , [72] , [54] , especially because gadolinium deposition in the brain has been described recently [73] . Bickelhaupt et al [69] , [70] proposed to use diffusion-weighted imaging with background suppression (DWIBS) for defining an ABB-MRI protocol and clarify mammogram based screening findings.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, there is a growing interest in the development of contrast-agent free protocols by using the acquisition of diffusion-weighted images (DWI) and their respective Apparent diffusion coefficient (ADC) maps [69] , [70] , [49] , [71] , [72] , [54] , especially because gadolinium deposition in the brain has been described recently [73] . Bickelhaupt et al [69] , [70] proposed to use diffusion-weighted imaging with background suppression (DWIBS) for defining an ABB-MRI protocol and clarify mammogram based screening findings.…”
Section: Resultsmentioning
confidence: 99%
“…Chen et al [49] showed that adding the diffusion to a protocol based on the first post-contrast sequence and MIP, significantly improves the performance of the protocol. Likewise, in 2018, Kul et al [72] conducted a study that seeks to establish the viability of using the acquisition of diffusion-weighted images and ADC map for describing the cellularity of masses detected in the breasts and to establish the contribution of this evaluation for its characterization. From the reported results, the diffusion images showed a high to moderate concordance during breast masses description respect to dynamic contrast-enhanced (DCE) study.…”
Section: Resultsmentioning
confidence: 99%
“…A further 103 studies were excluded for the study type (not articles), 40 studies were excluded for the language, and 111 studies were excluded for failure to meet the eligibility criteria after carefully reading the full text: failure to extract the number of true positives, false negatives, false negatives, and true negatives; no mp-MRI to diagnose breast cancer; and did not use 1.5-T or 3.0-T MRI machines. Finally, 22 studies were included in the meta-analysis (24,812,1417,2938).…”
Section: Resultsmentioning
confidence: 99%
“…While most previous papers focused on ADC values obtained from DWI, there are a few reports concerning morphological assessment of breast lesions using ss-EPI with an HR-DWI Using rs-EPI for Breast 1.5T MRI scanner. 30,31 Another report showed the additive diagnostic value in analysis of breast lesion using rs-EPI (voxel size: 2.1 × 1.8 × 4.0 mm 3 ) with a 3T MRI scanner. 23 These previous reports pointed out the value of less-distorted DWI.…”
Section: Discussionmentioning
confidence: 99%